Simulation of Two-Dimensional Scramjet Combustor Reacting Flow Field Using Reynolds Averaged Navier-Stokes WENO Solver (Communications in Computational Physics, 2020)
The non-equilibrium chemical reacting combustion flows of a proposed longslender scramjet system were numerically studied by solving the turbulent Reynoldsaveraged Navier-Stokes (RANS) equations. The Spalart-Allmaras one equation turbulencemodel is used which produces better results for near wall and boundary layerflow field problems. The lower-upper symmetric Gauss-Seidel implicit scheme, whichenables results converge efficiently under steady state condition, is combined with theweighted essentially non-oscillatory (WENO) scheme to yield an accurate simulationtool for scramjet combustion flow field analysis. Using the WENO schemes high-orderaccuracy and its non-oscillatory solution at flow discontinuities, better resolution ofthe hypersonic flow problems involving complex shock-shock/shock-boundary layerinteractions inside the flow path, can be achieved. Two types of scramjet combustorwith cavity-based and strut-based fuel injector were considered as the testing models.The flow characteristics with and without combustion reactions of the two types of combustor models were studied with a transient hydrogen/oxygen combustion model.The detailed results of aerodynamic data are obtained and discussed, moreover, thecombustion properties of varying the equivalent ratio of hydrogen, including the concentrationof reacting species, hydrogen and oxygen, and the reacting products, water,are demonstrated to study the combustion process and performance of the combustor.The comparisons of flow field structures, pressure on wall and velocity profilesbetween the experimental data and the solutions of the present algorithms, showedqualitatively as well as the quantitatively in good agreement, and validated the adequacyof the present simulation tool for hypersonic scramjet reacting flow analysis.